A passagem da moral à religião em Immanuel Kant - Zanella, Diego Carlos (2008)
To Immanuel Kant (1724-1804), moral and religion are bound up in some way, becoming different just by the fact that while moral, the duties are enacted as fundamental principles of every thinking human being, and by the fact that this one must act as a member of an ends universal system; while religion, those duties are seen as commandments of a supreme holy will, so that, the moral laws are the only ones which are in accordance with the idea of a supreme perfection. In the preface to the first edition of the Religion within the Boundaries of mere Reason Kant opens it with a claim moral is self-sufficient. Nevertheless, if morality in no way needs religion whether objectively (as regards willing) or subjectively (as regards capability), but it is self-sufficient; it is asked: why does religion consider the moral law as a commandment of a supreme holy will? Or yet, why is there a correlation between moral and religion? In this sense, its objective is to show how moral can reach its plenitude only in the absolute autonomy within the practice reason, which becomes law to itself as an unconditional and pure duty, and which can, then, indicate an inevitable relation existing between moral and religion. The connection between moral and religion, besides being fundamental and structural information of pure reason, it is the progressive recognition of a universal plan in which, despite all the liberty abuses by men, will reach in the end the highest possible degree of perfection of humankind.